Nutrient Dependent Cross-Kingdom Interactions: Fungi and Bacteria From an Oligotrophic Desert Oasis - Velez, Patricia; Espinosa-Asuar, Laura; Figueroa, Mario; Gasca-Pineda, Jaime; Aguirre-von-Wobeser, Eneas; Eguiarte, Luis E.; Hernandez-Monroy, Abril; Souza, Valeria (Frontiers in Microbiology, 2018)
Microbial interactions play a key role in ecosystem functioning, with nutrient availability as an important determinant. Although phylogenetically distant bacteria and fungi commonly co-occur in nature, information on their cross-kingdom interactions under unstable, extreme environments remains poor. Hence, the aims of this work were to evaluate potential in vitro interactions among fungi and bacteria isolated from a phosphorous oligotrophic aquatic system in the Cuatro Ciénegas Basin, Mexico, and to test the nutrients-based shifts. We evaluated growth changes in bacteria (Aeromonas and Vibrio) and fungi (Coprinellus micaceus, Cladosporium sp., and Aspergillus niger) on co-cultures in relation to monocultures under diverse nutrient scenarios on Petri dishes. Interactions were explored using a network analysis, and a metabolome profiling for specific taxa. We identified nutrient-dependent patterns, as beneficial interactions dominated in low-nutrients media and antagonistic interactions dominated in rich media. This suggests that cross-kingdom synergistic interactions might favor microbial colonization and growth under low nutrient conditions, representing an adaptive trait to oligotrophic environments. Moreover, our findings agree with the stress-gradient hypothesis, since microbial interactions shifted from competition to cooperation as environmental stress (expressed as low nutrients) increased. At a functional level consistent differences were detected in the production of secondary metabolites, agreeing with plate bioassays. Our results based on culture experiments, provides evidence to understand the complexity of microbial dynamics and survival in phosphorous-depleted environments.